Transcatheter pulmonary denervation in patients with left heart failure with reduced ejection fraction and combined precapillary and postcapillary pulmonary hypertension: A prospective single center experience. Issue 3 (8th February 2021) - Witkowski, Adam; Szumowski, Łukasz; Urbanek, Piotr; Jastrzębski, Jan; Skowroński, Jarosław; Sobieszczańska‐Małek, Małgorzata; Hoffman, Piotr; Kowalik, Ewa; Wiśniewska, Joanna; Banasiak, Adam; Parulski, Adam; Zieliński, Tomasz
Abstract: Objectives: The present study was a prospective, single‐center, single‐arm study to investigate the efficacy of transcatheter pulmonary artery denervation (TPADN) in patients with combined postcapillary and precapillary PH (Cpc‐PH) associated with left heart failure with reduced ejection fraction (HF‐rEF). Background: Pulmonary hypertension (PH) in patients with left ventricular systolic dysfunction has a negative impact on outcome. Methods: The combination of pulmonary artery systolic pressure (PAPs) ≥60 mmHg, transpulmonary pressure gradient (TPG) ≥12 mmHg, nonreversible mean PAP, and pulmonary vascular resistance (PVR) ≥3.5 Wood Units was considered as too high risk for heart transplantation (HTx). The clinical efficacy endpoint was an improvement in 6‐min walking test and the hemodynamic endpoints were changes in PAPs, PVR, and TPG between baseline and 6 months. Circumferential radiofrequency applications were delivered around distal main, left and right pulmonary arteries. At each ablation point temperature was 45°C and energy 10 W. Results: TPADN was performed in 10 patients. At 6‐month in 5 patients we observed reduction in PAP, PVR, TPG, and DPG and then 1 had successful HTx, 2 are on HTx waiting list, 2 received LVADs, 2 patients did not improve, and 3 patients died. Conclusions: TPADN may be beneficial in selected patients with HF‐rEF and Cpc‐PH.